Effect of flowing water on the pharmacokinetic properties of norfloxacin in channel catfish (Ictalurus punctatus) after single‐dose oral administration - Yali Yu; Lixue Dong; Lang Zhang; Jinhua Gan; Jie Peng; Ting Liu; Jianwu Chen; Xiaorong Lu; Li He; Bo Cheng (Veterinary Medicine and Science, 2023)
Abstract Background The recirculating aquaculture system (RAS) is a widely used, water‐saving and efficient aquaculture model. However, bacterial diseases are common in farmed fish reared at high densities. Although antibiotics effectively treat these diseases, developing efficient methods to increase drug clearance in fish and decrease the concentrations of antibiotic residues in aquatic products is essential. Objectives This study evaluates the effect of flowing water in the RAS on norfloxacin (NOR) pharmacokinetics in channel catfish (Ictalurus punctatus). Methods Channel catfish were randomly divided into the control group (RAS group) and the experimental group (flow‐through aquaculture system group) (120 individuals/group). A NOR dose of 20 mg/kg was then orally administered to the fish. Plasma, muscle, liver and kidney samples were collected up to 168 h after treatment. NOR concentrations were measured using liquid chromatography–mass spectrometry, and pharmacokinetic parameters were calculated using a non‐compartmental method. Results Flowing water had a significant effect on the plasma pharmacokinetics and tissue distribution of NOR, increasing NOR clearance in the kidney, muscle and plasma. The time to maximum concentration of NOR was shorter in the plasma and longer in the kidney and liver. Moreover, flowing water increased the maximum concentration of NOR in the kidney, muscle and plasma and decreased the area under the concentration–time curve from time 0 to the last measurable concentration in the liver and plasma. Flowing water decreased the withdrawal period in muscle from 10 to 6 days. Conclusions These results indicate that flowing water can potentially increase NOR clearance in channel catfish.